Penerapan Metode Waterfall pada Teknologi Sistem Informasi Web dalam Pelayanan Publik Pemerintah Daerah: Studi Kasus pada PTSP Kabupaten Banyuasin - Nisyah, Berlia; Algandi, Ahmad Jibrael; Suhanda, Janu; Purwani, Fenny (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Digital platforms known as web-based public service information system technology encourage increased effectiveness and quality of public services. The purpose of this study on web-based public service information systems is to simplify, accelerate, and make it more transparent for the general public to access services offered by local governments. Humans use information technology to handle information and information needs from organizational procedures. The community will find it easier to carry out administrative service procedures at the village level using this system because it is developed using the Waterfall development method. According to the findings of the study, the Banyuasin government's public service procedures should be faster to manage data, ensure more accurate data, and increase worker efficiency. Communities and local governments can benefit from this research by utilizing information technology more effectively.